Prevention of rhesus immunization in the presence of a potential sensitizing factor (Texas Journal of Medical Science, 2023)
In this article, prevention of rhesus immunization in the presence of a potential sensitizing factor, the development of hemolytic disease of fetuses and infants, and disorders of fetal erythrocytes are described in detail